2022
DOI: 10.12688/aasopenres.13272.1
|View full text |Cite
|
Sign up to set email alerts
|

Competency-based Training Needs Assessment for Research Managers and Administrators in Africa and the United Kingdom to Strengthen Equitable Partnerships

Abstract: Background: The need for competent research managers and administrators (RMAs) has increased due to the complexity in managing research projects between disparate and international partners. To facilitate the creation of robust training and professional development programmes it is essential to first understand the status quo. A collaborative project, Sustainable Management and Administration for Research: Training across the project Lifecycle (SMARTLife), made up of RMAs from South Africa, Zimbabwe and the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…It appears that RMA is a dominantly female profession although additional research is needed to reach reliable conclusions. These findings are broadly consistent with previous findings in Europe (Virágh et al, 2019) and globally (Kerridge & Scott, 2018a;Oliveira, Trindade, et al, 2022;Shambrook & Roberts, 2011), although Nembaware et al (2022) have found that African countries have twice as many male RMAs compared to the UK. RMA professionals are mostly situated within public HEI/Research Performing Organisations (RPOs).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It appears that RMA is a dominantly female profession although additional research is needed to reach reliable conclusions. These findings are broadly consistent with previous findings in Europe (Virágh et al, 2019) and globally (Kerridge & Scott, 2018a;Oliveira, Trindade, et al, 2022;Shambrook & Roberts, 2011), although Nembaware et al (2022) have found that African countries have twice as many male RMAs compared to the UK. RMA professionals are mostly situated within public HEI/Research Performing Organisations (RPOs).…”
Section: Discussionsupporting
confidence: 92%
“…One of the possible explanations may be the high costs associated with the EARMA membership and additional costs of attending conferences and competencybased training programmes that are not affordable to many RMAs from the WB. In addition to this, some scholars have contended that existing training programmes for RMAs are mainly available in the north and likely to differ between countries offering content that does not equally address the needs of less developed countries (Campbell, 2010;Nembaware et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors covering the issue of professional associations highlight the added value of RMA associations in the provision of trainings (Nembaware et al, 2022), opportunities for professional development (Kirkland, 2005c;Kirkland & Stackhouse, 2011;Nembaware et al, 2022), peer learning (Poli, 2018a;Kirkland & Ajai-Ajagbe, 2013) and networking (Kirkland & Ajai-Ajagbe, 2013). In addition, Langley and Ofosu (2007) underline the opportunity for sharing best practices and offering support to each other as the key values of such associations, referring to the examined associations as 'sustainable self-help organisations that disseminate good practice across the regions.…”
Section: Literature Reviewmentioning
confidence: 99%